Efficient GRE Techniques for the Scattering of Three-Dimensional Arbitrarily Shaped Deep Cavities - Wang, Shumin; Li, Mingzhi; Wang, Changqing; Zhu, Xili (Applied Computational Electromagnetics Society Journal (ACES), 2022)
An efficient implementation of the Generalized Ray Expansion (GRE) method for computing the scattering of three-dimensional (3-D) arbitrarily shaped deep cavities is studied in this paper. Efficiency is being sought from two aspects: ray racing in discrete cavities and reflection from individual patches. An improved algorithm for detecting intersections between a ray and triangular patches has been proposed, which is about 2.83 times faster than the traditional algorithm. Also, sectional algorithm and Wavefront Advancing and Candidate Narrowing (WACN) algorithm for tracing rays inside 3-D cavities are proposed to boost efficiency. As to reflection from individual patches, different local cavity reconstruction methods are being tested and interpolative triangular patches are found to be an efficient choice. Finally, several numerical examples further demonstrate the versatility and validity of our approach